AN ANALYSIS OF ENGLISH SUBTITLE IN THE MOVIE7 HATI 7 CINTA 7 WANITA - Galih Sapta Kusumah, - (2014)
The research is aimed at determining the subtitling strategies that arc used in thc movie 7 Hati 7 Cinta 7 Wanita as wetl as investigating the cases and the ways in which the subtitling strategies are used. A non-probability sampling method was employed to collect 525 pairs of dialogues-and-subtitles. The data were analyzed by using a qualitative method with Gottlieb's (1994) theory of subtitling strategies. In contrast to what Gottlieb states that condensation is typically the most-used strategy, the research showed that the most-used strategy was paraphrase (30.30%), while the least-used stratcgy was transcription (0.17%). Paraphrase strategy was used for many syntactic forms that could not be rendered easily. This strategy was used by changing the translation of source text into more sentences, proper nouns into personal pronouns, as well as changing sentence types and question forms to achieve greater clarity. On the other hand, transcription was applied limitedly in a dialogue that consists of an unusual term. This strategy was only used once by maintaining the term in the subtitle. Nevertheless, the significance of the use of subtitling strategies might be affected by the data material, the subtitler, and the size of the data.